2015
DOI: 10.3201/eid2103.141838
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ebola Virus Infection with Antibodies from Reconvalescent Donors

Abstract: Clinical evidence suggests that antibodies from reconvalescent donors (persons who have recovered from infection) may be effective in the treatment of Ebola virus infection. Administration of this treatment to Ebola virus–infected patients while preventing the transmission of other pathogenic viruses may be best accomplished by use of virus-inactivated reconvalescent plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…For example, recent clinical evidence suggests that Abs present in Ebola virus–infected convalescent immune sera contribute to improved clinical outcomes in infected patients (Kreil, 2015; Lyon et al, 2014) and recently vesicular stomatitis virus (VSV) vaccination has been shown to drive robust humoral immune responses (Regules et al, 2015) that provide protection from infection (Henao-Restrepo et al, 2015). However, the specific mechanism(s) by which Abs provide protection remains unclear.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…For example, recent clinical evidence suggests that Abs present in Ebola virus–infected convalescent immune sera contribute to improved clinical outcomes in infected patients (Kreil, 2015; Lyon et al, 2014) and recently vesicular stomatitis virus (VSV) vaccination has been shown to drive robust humoral immune responses (Regules et al, 2015) that provide protection from infection (Henao-Restrepo et al, 2015). However, the specific mechanism(s) by which Abs provide protection remains unclear.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Furthermore, the administration of these antibodies likely prevents virus infection/replication/dissemination within the patient, rather than virus clearance. An important prerequisite to prevent infection with bloodborne diseases is that safety of virus-inactivated convalescent plasma transfusions is guaranteed, which can be challenging in EVD endemic areas [27]. Clinical trials were initiated in Guinea, Sierra Leone, and Liberia; without severe adverse reactions reported to date.…”
Section: Convalescent Plasma (Polyclonal Antibody Therapy)mentioning
confidence: 99%
“…The largest outbreak of Ebola virus infection is discussed in Ref. [88]. Such advanced superiorities would be perfect for fast, point-of-care detection of Ebola virus [89].…”
Section: Ebolamentioning
confidence: 99%